Adjustment of self-initiated and organizational expatriates: The moderating role of cross-cultural training - Noman, Muhammad; Sial, Muhammad Safdar; Samad, Sarminah; Li, Rita Yi Man; Shi, Miao (Frontiers in Psychology, 2023)
Globalization and the international labor movement made the ability to work anywhere globally. These individuals are usually organizational expatriates (OEs) deployed to overseas assignments by their employers or self-initiated expatriates (SIEs) who choose to relocate and work in a foreign country. Therefore, this study examines and contrasts the variations in cross-cultural adjustment (CCA) between Chinese SIEs and OEs in Pakistan. Furthermore, the study seeks to understand how cross-cultural training (CCT) influences the adaptation of Chinese SIEs and OEs. Data were obtained from 35 Chinese expatriates with 17 SIEs and 18 OEs employing a qualitative technique and were analyzed via thematic analysis in MAXQDA 20. According to the study, both SIEs and OEs face distinct hurdles to their CCA in Pakistan, including cultural taboos, language obstacles, and work variations. While numerous aspects that will favorably affect their CCA, including the accessibility of basic necessities, the friendliness of the Pakistani people, and the brethren relations between Pakistan and China, assist them in making a smooth transition to life in Pakistan. Furthermore, the results indicate that the mediating role of pre-departure CCT and the host country mentors' support and facilitations acquired through online resources contribute to both Chinese SIEs and OEs' CCA in Pakistan.